Comparative value of dry-rolled corn, distiller’s dried grains, and wheat middlings for receiving diets - Ives, S.E.; Anderson, D.W.; Wessels, R.H.; Drouillard, James S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two 28-day receiving experiments were conducted using 620 exotic × British cross steers to evaluate differences in growth performance, morbidity, and mortality when fed diets containing dry-rolled corn, distiller’s dried grains with solubles, or wheat middlings. All diets contained approximately 60% concentrate and 40% roughage (alfalfa hay). Gain and efficiency tended to be poorer for cattle fed the wheat middling-based diet than for those fed corn. No notable differences were evident in terms of the percentage of cattle treated for respiratory disease. Feed intake and daily gain were improved slightly when corn was replaced by distiller’s dried grains, but efficiency was not changed. However, the incidence of respiratory disease also was higher for cattle fed the distiller’s grains diet in comparison to corn.
Keywords: Beef; Distiller’s grains; Wheat middlings; Receiving cattle; Health